Haematic Potentials of Rhynchospora Corymbosa and Olax Subscorpioïdea Extract in Phenylhydrazine – induced Anaemic Rats - Soro, M’béfèhê; Akakpo-Akue, Joël; Bognan Ackah, Jacques Auguste Alfred; Sibri, Jean-François; Yapi, Yayé Guillaume; Mireille Kple, Tatiana Kangah; Getheme Sanko, Sihi Ephrem Léangeovers (European Scientific Journal, ESJ, 2023)
The decoction of the whole plant of Rhynchospora corymbosa and Olax subscorpioïdea leaves are used by the Local traditional healers in the department of Korhogo (Northern Côte d’Ivoire) to treat patients with sickle cell disease. This study was designed to assess, the antianemic potential of these plants extract. Anemia was induced with phenylhydrazine hydrochloride in rats. Animals were divided in normal (N), control (C), test (T), and reference (R) groups. T group included ill-induced Animals treated with R. corymbosa and O. subscorpioidea extracts, and R group ill-induced animals treated with vitamin B9 for anemic animals. Dosing was made as 1-day single dose repeated dose. In anemic animals, the production rate of RBC was significantly (p < 0.001) higher in T group as compared to C group. R. corymbosa whole plant and O. subscorpioidea leaves extracts have a haematic potential. The anti-anaemic effect may partly explain their use in patients with sickle cell disease who are affected by a deficiency of erythrocytes and its components.